2013
DOI: 10.1089/jir.2012.0129
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by New Glucocorticoid Antedrugs [16α, 17α-d] Isoxazoline and [16α, 17α-d]-3′-Hydroxy-Iminoformyl Isoxazoline Derivatives of Chemotaxis and CCL26, CCL11, IL-8, and RANTES Secretion

Abstract: The underlying inflammation present in chronic airway diseases is orchestrated by increased secretion of CC and CXC chemokines that selectively recruit the leukocyte populations into the pulmonary system. Human chemokines, eotaxins (CCL11 and CCL26), RANTES, and interleukin (IL)-8, are dramatically upregulated through G-protein receptors in cell inflammation, including human asthma. In previous studies, a series of new glucocorticoid antedrugs (GCAs) were synthesized as derivatives of isoxazoline and oxime, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…It is known that the secretion of eotaxin is suppressed by glucocorticoids. 43,44 Furthermore, we demonstrated an increase of CD34…”
Section: Discussionmentioning
confidence: 59%
“…It is known that the secretion of eotaxin is suppressed by glucocorticoids. 43,44 Furthermore, we demonstrated an increase of CD34…”
Section: Discussionmentioning
confidence: 59%
“… 26 Application of this CCL5 antagonist can significantly inhibit the recruitment of inflammatory cells such as eosinophils and T lymphocytes, thus suppressing the development of allergic rhinitis. 27 , 28 Previous studies have shown that polymorphisms of RANTES are associated with asthma susceptibility. Zhang, YG 29 found that the RANTES gene-403G/A polymorphism may be a risk factor for patients with atopic asthma.…”
Section: The Specific Effects Of the Main Chemokines In The Process O...mentioning
confidence: 99%
“…IgE-binding proteins with MWs of 53 and 58 kDa were identified in three unrefined soybean oils [16]. A 56 kDa allergenic protein was also found in cold-pressed and deodorised soybean oils, which was later identified as soybean β-amylase (7S globulin), together with the 20 kDa allergen Kunitz Trypsin Inhibitor (KTI) [17,18].…”
Section: Soy Bean Oil As Source Of Allergensmentioning
confidence: 99%